The Relationship Between Macronutrient Intake Level and Nutritional Status with Agility in Karate Athletes at Lemkari Gianyar Ranting Ketewel - Ni Kadek Diah Putri Hariani; I Wayan Ambartana; Ni Nengah Ariati (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2026)
Agility is a crucial physical component in karate that allows athletes to rapidly change direction and body position without losing balance. This study aimed to analyze the relationship between macronutrient intake (carbohydrates, protein, and fat) and nutritional status with agility in karate athletes at Lemkari Gianyar Ranting Ketewel. This was an observational study with a cross-sectional design involving 40 karate athletes aged 10–16 years. Macronutrient intake data were collected using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), nutritional status was assessed based on BMI-for-age (BMI/Age), and agility was measured using the shuttle run test. Data were analyzed using the Spearman Rank Correlation test. Results showed that 50% of athletes had good agility, 65% had normal protein intake, 52.5% had normal fat intake, 52.5% had normal carbohydrate intake, and 70% had good nutritional status. Significant correlations were found between macronutrient intake and nutritional status, and between nutritional status and agility (p<0.05). It is recommended that athletes maintain a balanced diet and that coaches engage in nutrition education and monitoring.